Efektifitas penggunaan workshop di jurusan Teknik Sipil FT-UNP - Habil Fajrian; Yuwalitas Gusmareta (Teknik Sipil Universitas Negeri Padang, 2020)
Abstract : This study aims to determine the level of effectiveness of using workshop in the civil engineering department of UNP. This type of research is quantitative descriptive. The population in this study was 54 students of the 2018 FT-UNP building engineering study program who were active. Sampling was done using total sampling technique. The data then were analyzed statistically with the help of Microsoft excel 2019 and using the formula for degrees of Achievement (DP) from the result of data analysis it can be concluded that the effectiveness of using workshop in the civil engineering department of FT-UNP is classified as good, with the results of the degree of achievement (DP) of 80,52%.